Discovery and development of antidiabetic agents from natural products : natural product drug discovery - Brahmachari, Goutam (Natural product drug discovery., 2017)
Discovery and Development of Antidiabetic Agents from Natural Products brings together global research on the medicinal chemistry of active agents from natural sources for the prevention and treatment of diabetes and associated disorders. From the identification of promising leads, to the extraction and synthesis of bioactive molecules, this book explores a range of important topics to support chemists in the discovery and development of safer, more economical therapeutics that are desperately needed in response to this emerging global epidemic. Beginning with an overview of bioactive chemical compounds from plants with anti-diabetic properties, the book goes on to outline the identification and extraction of anti-diabetic agents and antioxidants from natural sources. It then explores anti-diabetic plants from specific regions before looking more closely at the background, isolation, and synthesis of key therapeutic compounds and their derivatives, including Mangiferin, Resveratrol, natural saponins, and alpha-glucosidase enzyme inhibitors. The book concludes with a consideration of current and potential future applications. Combining the expertise of specialists from around the world, this volume aims to support and encourage medicinal chemists investigating natural sources as starting points for the development of standardized, safe, and effective antidiabetic therapeutics.